2006
DOI: 10.1111/j.1540-8175.2006.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with Real‐Time Three‐Dimensional Echocardiographic Guidance of Right Ventricular Biopsy in Children

Abstract: The use of real-time transthoracic 3DE in endomyocardial right ventricular biopsies in children is both feasible and safe. Further study to determine the impact of real-time 3DE guidance on fluoroscopy and case times for endomyocardial biopsies is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Scheurer et al demonstrated the use of live 3DE to guide the performance of endomyocardial biopsy in children. 19 In their experience, the use of live 3DE guidance was associated with no complications, including no new tricuspid valve leaflet flail or pericardial effusion. 3DE proved to be a reliable noninvasive modality to accurately direct the bioptome to the desired site of biopsy within the RV.…”
Section: Image-guided Intervention: Transthoracic 3dementioning
confidence: 94%
“…Scheurer et al demonstrated the use of live 3DE to guide the performance of endomyocardial biopsy in children. 19 In their experience, the use of live 3DE guidance was associated with no complications, including no new tricuspid valve leaflet flail or pericardial effusion. 3DE proved to be a reliable noninvasive modality to accurately direct the bioptome to the desired site of biopsy within the RV.…”
Section: Image-guided Intervention: Transthoracic 3dementioning
confidence: 94%
“…Scheurer et al [20] reported the feasibility and utility of real-time transthoracic 3D echocardiography to guide RV endomyocardial biopsies in 28 consecutive cardiac catheterizations in children aged 18 months to 16 years who were undergoing endomyocardial biopsy. There were no complications, including no new tricuspid valve leaflet flail or pericardial effusion.…”
Section: Clinical Evaluation Of Right Ventricular Volume and Functionmentioning
confidence: 99%
“…Scheurer et al [ 44 ] demonstrated the use of live 3DE to guide the performance of endomyocardial biopsy in children. In their experience, live 3DE guidance was associated with no complications, including no new tricuspid valve leafl et fl ail or pericardial effusion.…”
Section: Image-guided Interventionsmentioning
confidence: 99%